Substitute symbolic sub-expression in expression

4 次查看(过去 30 天)
I have an equation
eq = Tnext - 2*Tn + Tprev == - sigma*Tinf^4*h^2 - alpha*Tinf*h^2 + sigma*Tn^4*h^2 + alpha*Tn*h^2
in which I want to replace the sub-expression
sigma*Tinf^4*h^2 - alpha*Tinf*h^2
with
C = sigma*Tinf^4*h^2 - alpha*Tinf*h^2
such that it becomes
eq = Tnext - 2*Tn + Tprev == - C + sigma*Tn^4*h^2 + alpha*Tn*h^2
I have tried the following:
eq_to_sub = sigma*Tinf^4*h^2 - alpha*Tinf*h^2;
syms C
eq = subs(eq, eq_to_sub, C)
subsx = @(u,w0,w0str) feval(symengine,'subsex',u,[char(w0) '=' w0str]);
eq = subsx(eq, eq_to_sub, 'C')
which doesnt change the equation at all. Weirdly, both methods work if the sub-expression (to substitute) is limited to
eq_to_sub = sigma*Tinf^4;
resulting in
Tnext - 2*Tn + Tprev == Tn*h^2*alpha - C*h^2 + Tn^4*h^2*sigma + (-h^2)*Tinf*alpha
  1 个评论
Valeri Aronov
Valeri Aronov 2021-6-27
Note that the monomials in C have different signs, but the same monomials in eq have the same sign. C is not found in eq because of it.

请先登录,再进行评论。

采纳的回答

Jyotsna Talluri
Jyotsna Talluri 2020-6-8
Enclose the subexpresssion in braces as it contains more than one term.
eq = Tnext - 2*Tn + Tprev == - (sigma*Tinf^4*h^2 + alpha*Tinf*h^2) + sigma*Tn^4*h^2 + alpha*Tn*h^2;
C = sigma*Tinf^4*h^2 + alpha*Tinf*h^2;
q = feval(symengine,'subsex',eq,[char(C) '=C']);
  2 个评论
Martin Androvich
Martin Androvich 2020-6-8
That's tricky, haha! But it works, so thanks a bunch 😊
Martin Androvich
Martin Androvich 2020-6-8
编辑:Martin Androvich 2020-6-8
But what if the expression is generated from some other function, e.g. simplify(), where I cannot simply manually enclose it in braces?

请先登录,再进行评论。

更多回答(0 个)

类别

Help CenterFile Exchange 中查找有关 Symbolic Math Toolbox 的更多信息

产品


版本

R2020a

Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!

Translated by